Silica Gel From Bagasse Ash for Methylene Blue Adsorption - Anisara, Raisa; Wardhani, Gladys Ayu Paramita Kusumah; Taufiq, Agus (Sains Natural: Journal of Biology and Chemistry, 2024)
Most silica sources are from non-renewable natural sand or rock materials, which affect the element's diminishing availability in the environment. Because bagasse ash has a relatively high silica concentration, it can be used as a silica source to manufacture silica gel. HCl is added during the sol-gel process of silica gel synthesis. The silica gel's characterization employs FTIR, XRD, and SEM instruments. Characterization results showed that silica gel contains silanol groups identified by the appearance of vibrations at the wavenumber of 3383,93 cm-1 and 1635,17 cm-1. Vibrations of the siloxane group appear at the wavenumber of 1020,83 cm-1 and 579,88 cm-1. Silica gel diffractogram showing dilated diffraction peaks at 2q = 22,90ᵒ. Silica gel has potential as an adsorbent in adsorbing methylene blue dye. The ideal parameters for the methylene blue adsorption process are pH 10 and 45 minutes of contact time., silica gel weight of 0.1 g, and methylene blue concentration of 100 mg/L. Using the Langmuir isotherm rule, the silica gel of bagasse ash has a high adsorption capacity of 56.818 mg/g.